Effects of Quercetin and ACTH on Morphine-Induced Tolerance and Dependence in Mice: Attenuation of morphine tolerance by quercetin - Habibi Asl, Bohlul; Delazar, Abbas; Assady, Malahat (Iranian Journal of Pharmaceutical Sciences, 2006)
The goal of this study was to evaluate the effects of quercetin and ACTH injection on prevention of development of morphine tolerance and dependence in mice. In this study different groups of mice received morphine (40 mg/kg, i.p.) plus quercetin (5, 10, 25 mg/kg, ip), ACTH (1, 2.5, 5 IU/mice, i.p.), or combination of quercetin (5 mg/kg) and ACTH (1 IU/mice) once a day for four days. Tolerance was assessed by administration of morphine (9 mg/kg) and using hot plate test on the fifth day. It was found that pretreatment with quercetin or ACTH decreased the degree of tolerance. Co-administration of quercetin and ACTH before morphine did not decrease the tolerance, significantly. From these results it may be concluded that administration of quercetin or ACTH alone could prevent the development of tolerance to the analgesic effects of morphine. These effects may be related to as nitric oxide inhibitor (eNOI) behavior of quercetin and the ability of morphine and their receptors in the control of the secretion of CRH.